The Role of ‘Ngalap Barokah’ in Rapid Urban Development: Case Study of Tebuireng, Jombang - Hanifa Fijriah; Evawani Ellisa (Journal of Islamic Architecture, 2022)
The purpose of this paper is to identify the background of rapid urban development in Tebuireng, an area hosting one of the oldest and most well-known pesantren (Islamic boarding school) in Indonesia. Within less than a decade, Tebuireng has run into significant development to accommodate massive number of people visiting the area. We conduct numerous field observation, mappings and in-depth interview with related actors in the area. Content analysis method is carried out to figure out the objective of this research. The study found that faith, known as ‘Ngalap Barokah’ is the main basis for the process of city formation and determines how the urban actors utilize the urban space. Considering the huge numbers of Islam believers in Indonesia, it is important to understand the aspects of faith that affect the urban growth, especially in the cities dominated by Moslem population. Finally, the finding of this faith based morphological research is potentially contributed for the practice of Indonesian urban planning, especially for anticipating the city growth dominated by Moslem stake holders.